Penetapan Kadar Fenolik dan Flavonoid Total Ekstrak Etanol Buah Parijoto (Medinilla speciosa Blume) dengan Metode Spektrofotometri UV-Vis - Prashinta Nita Damayanti; Fania Putri Luhurningtyas; Lyna Lestari Indrayati (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2023)
Parijoto (Medinilla speciosa) has a wide range of pharmacological activities due to its secondary metabolite content, especially flavonoid, and phenolic compounds. Flavonoid and phenolic compounds have a major role in human health with their activities as antioxidants, anti-inflammatories, antimicrobials, etc. This study aimed to determine the total levels of phenolic and flavonoid compounds from the ethanol extract of Parijoto fruit. Parijoto fruit is obtained from Bandungan, Semarang Regency, Central Java. Extraction was carried out by maceration method with 70% ethanol solvent then concentrated using a rotary evaporator. The total phenolic and flavonoid content amount was determined using the colorimetric method with Folin-ciocalteau complex reagent on phenolic with gallic acid as the reference standard and AlCl3 complex reagent on flavonoids with quercetin as the reference standard. Absorbance was measured using a UV-Vis spectrophotometer. The results showed that the color of the viscous extract of Parijoto fruit was dark brown with a yield of 6.67% w/w. The total phenolic content of the ethanol extract of Parijoto fruit was 21.67 µgGAE/g extract and the total flavonoid content was 9.21 µg QE/g extract.